Plastic Change along the Intact Crossed Pathway in Acute Phase of Cerebral Ischemia Revealed by Optical Intrinsic Signal Imaging. (6th April 2016) - Guo, Xiaoli; He, Yongzhi; Lu, Hongyang; Li, Yao; Su, Xin; Jiang, Ying; Tong, Shanbao
Abstract : The intact crossed pathway via which the contralesional hemisphere responds to the ipsilesional somatosensory input has shown to be affected by unilateral stroke. The aim of this study was to investigate the plasticity of the intact crossed pathway in response to different intensities of stimulation in a rodent photothrombotic stroke model. Using optical intrinsic signal imaging, an overall increase of the contralesional cortical response was observed in the acute phase (≤48 hours) after stroke. In particular, the contralesional hyperactivation is more prominent under weak stimulations, while a strong stimulation would even elicit a depressed response. The results suggest a distinct stimulation-response pattern along the intact crossed pathway after stroke. We speculate that the contralesional hyperactivation under weak stimulations was due to the reorganization for compensatory response to the weak ipsilateral somatosensory input.